Investigations of the humidity sensing properties of side-chain-type sulfonated poly (arylene ether ketone)s. (November 2019) - Meng, Fanting; Zhuang, Zhuang; Zhang, Yurong; Na, Hui
Side-chain-type sulfonated poly (arylene ether ketone)s containing naphthalene moieties with a degree of sulfonation (Ds) from 0.2 to 1.9 were synthesized. Humidity sensors were fabricated by cast coating on silver–palladium interdigital microelectrodes. The properties of this series of materials in terms of water absorption, glass transition temperature, and humidity sensing were characterized in detail. The investigations on the humidity sensing performance showed that with the increase in the Ds, the hysteresis of our materials exhibits an increasing trend first, followed by a decrease. This special phenomenon has not been reported before and caught our attention. From the results of humidity sensing properties, among the materials, the one with 0.2 Ds is promising for applications in humidity sensing due to its small hysteresis and fast response to varied relative humidity (RH). For a better understanding of the humidity sensing behavior of the sensor, complex impedance spectra were also measured. In the long-term stability measurement, the deviation of the measured impedance of the sensor at 97% RH is not obvious, proving good stability in a humid environment.